ANALISIS KEMAMPUAN KOMUNIKASI MATEMATIS SISWA SMP PADA MATERI BANGUN RUANG SISI LENGKUNG - Juliana Purba; Maimunah Maimunah; Yenita Roza (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2020)
Learning Mathematics requires students to have mathematical communication skills. This study aims to analyze the communication skills of students on the curved side solid figure material. The type of the research is descriptive qualitative research. The subjects of this study were 6 highly skilled students, medium and low ability students selected from 24 students of SMP Negeri 33 Pekanbaru in 2019/2020. The used data collection technique was tests and interviews. The conclusion of the analysis of this research is the communication skills of high-ability students with students who have reached the communication skills indicator. Inhibiting factors that support highly capable students are reading and writing factors. Groups that are capable are in the moderate category while students are only able to reach indicators in defining, re-approving mathematical ideas and linking real problems to solve problems, connecting factors that support capable students who are reading, searching and understanding material. Low-ability groups are still in the poor category among students only able to achieve indicators defining and supporting mathematical ideas to solve problems, factors related to low-ability students are prerequisite knowledge factors, reading, writing and understanding material.